The counter-narrative: U.S. non-proliferation policy towards Pakistan from Ford to Clinton - Akhtar, Rabia (Kansas State University, 2015)
Best known for being a ‘rollercoaster’ and a ‘marriage of convenience’, various scholars have tried to reflect upon the true nature of Pak-U.S. relationship under this banner. However, no matter how one examines this relationship one thing is certain –– the experience for both countries has been harrowing. After India settled for non-alignment early in the Cold War, Pakistan seized the opportunity and aligned itself with the United States in the East-West struggle and pledged allegiance to fight communism in Asia. But that was not the only motive –– Pakistan secretly hoped that an alliance with the U.S. would provide it security against India with whom Pakistan had an antagonistic relationship over their outstanding territorial dispute of Kashmir. When the U.S. did not rescue Pakistan as it had hoped for during its war with India in 1965 and sanctioned both countries with an arms embargo, Pakistan felt betrayed. From that period onwards, Pakistan’s list of grievances against the U.S. developed into a narrative of betrayal and abandonment fed by several episodes in their relationship during and after the Cold War –– a period in which Pakistan developed and tested its nuclear weapons –– duly exploited by Pakistani leaders as a tool for populist politics. This dissertation provides the first scholarly account of Pakistan’s narrative and tests its merit against the U.S. non-proliferation policy towards Pakistan under five administrations from Ford to Clinton and finds that Pakistan’s narrative of betrayal and abandonment is uneven and misleading with respect to the objectives and successes of U.S. non-proliferation policy. This dissertation uses multi-archival documents to offer a counter-narrative which argues that Pakistan, although a small state, was able to brilliantly maneuver its way through restricted spaces in its relationship with the U.S. in the past five decades to not only acquire a decent conventional capability through U.S. military assistance but also nuclear weapons due to the fickleness of U.S. non-proliferation policy. This research concludes that the compromises made by the U.S. to accommodate Pakistan and its inconsistency in enforcement of non-proliferation laws has implications for the efficacy and success of U.S. non-proliferation policy with prospective proliferants.
Keywords: Non-proliferation; Pakistan; Nuclear weapons; PaK-U.S. relations